Dopamine-dependent changes in the functional connectivity between basal ganglia and cerebral cortex in humans. - Williams, D; Tijssen, M; Van Bruggen, G; Bosch, A; Insola, A; Di Lazzaro, V; Mazzone, P; Oliviero, A; Quartarone, A; Speelman, H; Brown, P (2002)
We test the hypothesis that interaction between the human basal ganglia and cerebral cortex involves activity in multiple functional circuits characterized by their frequency of oscillation, phase characteristics, dopamine dependency and topography. To this end we took recordings from macroelectrodes (MEs) inserted into the subthalamic nucleus (STN) in eight awake patients following functional neurosurgery for Parkinson's disease. An EEG was also recorded, as were the signals from MEs in the globus pallidus interna (GPi) in two of the cases. Coherence between EEG and ME potentials was apparent in three major frequency bands, 2-10 Hz, 10-30 Hz and 70-85 Hz. These rhythmic activities differed in their cortical topography, although coherence was always strongest over the midline. Coherence between EEG and ME potentials in the 70-85 Hz band was only recorded in patients treated with levodopa. Cortical activity phase led that in the basal ganglia in those oscillatory activities with frequencies <30 Hz. In contrast, STN and GPi phase led cortex in the 70-85 Hz band. The temporal differences in the way in which cortical activity led or lagged behind that in STN/GPi were similar, around 20 ms, regardless of the overall direction of information flow and frequency band. We conclude that the basal ganglia may receive multiple cortical inputs at frequencies <30 Hz and, in the presence of dopaminergic activity, produce a high frequency drive back to the cerebral cortex, in particular the supplementary motor area (SMA).